The Integrity of the General Election Commission is Tested on the Failed Verification of the Ummat Party for the 2024 General Election - Vicki Dwi Purnomo; Hartanto (PT FORMOSA CENDEKIA GLOBAL, 2023)
At this time the Republic of Indonesia is preparing to carry out a democratic party to welcome the 2024 general election, currently various problems have occurred along with the preparation for the election itself. The first problem is the readiness of the political party information system which is still problematic, coupled with the problem of party verification which had reaped polemics as well as bad rumors about the KPU leadership itself that appeared in media reports. Serious studies and good integrity are needed to make the KPU an institution that is trusted by the public. Considering that our nation has been independent for more than 77 years, we need to be serious about running the 2024 democratic party.